Cultural translation : kolegij prof. Aidana O'Malleya, PDS književnosti, izvedbenih umjetnosti, filma i kulture, akad. god. 2009/2010 : čitanka - O'Malley, Aidan; Friel, Brian; Kilroy, Thomas; Heaney, Seamus; Eagleton, Terry; Bermann, Sandra; Steiner, George; Venuti, Lawrence; Paulin, Tom; Cronin, Michael; Benjamin, Walter (2009)
Cultural Translation

Seminar 1: Introduction to theories of translation and to the broad background to the literary texts.

Seminar 2: ‘Translating the Past’
Texts: Brian Friel, Translations and Making History; George Steiner, After Babel (exerpts)

Seminar 3: ‘Sophocles and the Limits of Justice and Resolution’
Texts: Tom Paulin, The Riot Act; Seamus Heaney, The Cure at Troy; Walter Benjamin, ‘The Task of the Translator’

Seminar 4: ‘Hosting Chekhov’
Texts: Brian Friel, Three Sisters; Frank McGuinness, Uncle Vanya; Lawrence Venuti, domesticating and foreignising translations.

Seminar 5: ‘Translating the Self’
Texts: Thomas Kilroy, Double Cross; Terry Eagleton, Saint Oscar; Adam Roberts, ‘On Translating a Person’

This course unfolds how the act and idea of translation can provide an optic through which the role of literary texts in the world can be read. Every translation involves a series of ethical choices; between, for instance, the need to attend to the spirit and/or the letter. These choices, however, never allow for the possibility of one correct interpretation and are instead inherently ambiguous, and this course explores the relationship between this contradictory ethics and the ways in which literature shapes notions of cultural and personal identity.

In order to do this, we will bring into dialogue some key texts in translation studies with a set of dramas. The seminars are devoted to exploring how themes that are performed in the plays might be understood in terms of an ethics of translation. These themes include: the writing of history, the possibility of resolution, the act of hospitality and the performance of the self. Phrasing these in terms of translation further involves examining the role of translation in poststructuralist, hermeneutic, psychoanalytical and postcolonial thinking.

The dramas that are examined were all produced by Field Day, a cultural intervention into the Northern Irish ‘Troubles’ that is also credited with introducing postcolonial discourse into Irish Studies. Knowledge of this group, or of Irish history and literature, is not required for this course; rather these literary texts and this background provide specific aesthetic, historical and political contexts to the theoretical discussions of the trope and act of translation.
Friel, Brian, Making history
Friel, Brian, Translations
Friel, Brian, Three sisters
Kilroy, Thomas, Double cross
Heaney, Seamus, The cure at Troy
Eagleton, Terry, Saint Oscar
Bermann, Sandra, Introduction (iz: Nation, language and the ethic of translation)
Steiner, George, The hermeneutic tradition
Venuti, Lawrence, The translator's invisibility (pp ix-34)
Paulin, Tom, The riot act
Cronin, Michael, Translation and minority languages in a global setting (iz: Translation and globalization)
Benjamin, Walter, The task of the translator
F
Keywords: književno prevođenje